Valuation of Credit Derivatives with Multiple Time Scales in the Intensity Model - Beom Jin Kim; Chan Yeol Park; Yong-Ki Ma (Journal of Applied Mathematics)
We propose approximate solutions for pricing zero-coupon defaultable bonds, credit default swap rates, and bond options based on the averaging principle of stochastic differential equations. We consider the intensity-based defaultable bond, where the volatility of the default intensity is driven by multiple time scales. Small corrections are computed using regular and singular perturbations to the intensity of default. The effectiveness of these corrections is tested on the bond price and yield curve by investigating the behavior of the time scales with respect to the relevant parameters.